Marginal employment: Stepping stone or dead end? Evaluating the German experience - Ronny Freier; Viktor Steiner (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2008)
'Marginal employment', i. e. employment with low working hours and earnings not covered by social security, has been gaining importance in the German economy over the past decade. Using a large newly available panel data set from the Employment Statistics of the Federal Employment Agency and statistical matching techniques, we analyse the effects of marginal employment on future individual outcome variables such as unemployment, regular employment and earnings. In addition to average treatment effects, we calculate dynamic and cumulative treatment effects accounting for total time spent in various labour market states and related earnings over a period of three years. We restrict the analysis to men and estimate the treatment effects separately for eastern and western Germany as well as for older workers and those workers who are likely to top up unemployment benefits with earnings from marginal employment. We find that marginal employment (i) does not affect time spent in regular employment within a three-year observation period, (ii) reduces future unemployment, where (iii) the effects on unemployment are to be seen as transitory. Furthermore, it (iv) slightly increases cumulated future earnings on average, and (v) is associated with a small negative cumulative earnings effect for older workers in western Germany.
Keywords: 330; geringfügige Beschäftigung - Auswirkungen; Berufsverlauf; Beschäftigungseffekte; Einkommenseffekte; Arbeitslosigkeit; Erwerbstätigkeit; regionaler Vergleich; Mini-Job; arbeitslose Männer; Substitutionseffekte; BA-Beschäftigtenpanel; Ostdeutschland; Westdeutschland; Bundesrepublik Deutschland